Political participation and party capture in a dualized economy: A game theory approach - Kim Leonie Kellermann (Westfälische Wilhelms-Universität Münster, Centrum für Interdisziplinäre Wirtschaftsforschung (CIW), 2017)
This paper examines the link of political participation and employment status in a dualized labor market. Both insiders and outsiders can actively take part in political decision-making, e.g. by voting for a certain party. Insiders only have the resources to also provide financial donations to policy-makers. Future policy outcomes are determined in a dynamic two-stage game. First, individuals choose their optimal quantity of support depending on policy strategies. Second, parties determine their optimal policy platform anticipating the individual behavior. In order to collect donations, parties are incentivized to occupy an insider-friendly position. Thereby, insiders are encouraged to participate in politics while outsiders are discouraged. Labor market dualization opens up a gap in political involvement which induces a reinforcement of economic segmentation. However, party capture by insiders is weaker, the more strongly a party is originally tied to outsiders. With two parties competing for support and donations, political inequality becomes firmly established since both parties fully adopt the insiders' preferences.
Keywords: D71; D72; J42; P16; 330